Pengaruh Fasilitas Kerja Terhadap Efektivitas Kerja Pegawai Kantor Badan Kepegawaian Daerah Provinsi Maluku - Merry Watloly; Jean Rosalina Asthenu; Carla Caroline Tousalwa; Vascolino Pattipeilohy (P3M Politeknik Negeri Ambon, 2025)
This study aims to analyse the Influence of Work Facilities on Employee Work Effectiveness at the Regional Personnel Agency of Maluku Province. Work Facilities that can affect Employee Work Effectiveness. This study was conducted at the Regional Personnel Agency of Maluku Province to determine whether Work Facilities affect Employee Work Effectiveness.This study uses a quantitative, survey-based approach, collecting data through questionnaires distributed to employees of the Regional Personnel Agency of Maluku Province. The sample in this study consisted of 44 employees. The method used in this study is a simple linear regression analysis in SPSS version 26; the regression equation Y = 25.305 + 0.195X is obtained. From the results of the hypothesis study, the t-count value is 2.113 with a probability of 1.68 or (p <0.05)The results of the independent variable (work facilities) research on the dependent variable (employee work effectiveness) are 0.95%, while the remaining variance is influenced by other variables. Based on the study's results, it can be concluded that work facilities have a positive and significant effect on employee work effectiveness at the Maluku Provincial Regional Personnel Agency. Keywords: Work Facilities and Work Effectiveness